Impact of Faculty development program (FDP) on faculty’s professional Development - Saima Rafique; Maimoona Nasreen; Abeera Fatima; Javeria Usman; Zakia Saleem; Lubna Baig (Journal of University Medical & Dental College, 2025)
BACKGROUND AND OBJECTIVE: Faculty Development Program (FDP) represents a purpose-built educational program that helps medical teachers build their competency and increase their effectiveness in curriculum delivery. Moreover, such programs offer an additional opportunity for professional growth, leadership development, and scholarly pursuits. This study explores faculty members' perceptions about the impact of FDP on their professional development.METHODOLOGY: This is a qualitative exploratory study conducted through focus group discussions (FGDs) with University College of Medicine (UCM) faculty members who had various academic ranks. The research team employed purposive sampling to select members from UCM who had maintained membership for five years and participated in two or more FDPs annually. Thematic analysis of the transcripts was performed using manual coding and N Vivo 12 software. Triangulation of data was achieved through member checking, combined with analysis by two independent researchers.RESULTS: Thematic analysis identified three main themes: Positive Impact of Workshops (PIW) as the primary finding, with "Opportunities for Continuing Medical Education (CME) at the Workplace," "Improved Teaching Methodologies," "Better Assessment Construction," and "Enhanced Workplace Well-being" as its subcategories. Career Development Opportunities (CDO) contained five subcategories under its theme: “Motivation”, Transforming Shared Passion”, “Capacity Building “and Opportunities for Enhanced Collaboration and Mentorship and Guidance. The study participants specified Key important improvement areas (KIA), which included integrating new technologies as well as developing asynchronous content for basic-level workshops.CONCLUSION : FDP is essential for optimal delivery of curriculum and should addresses newer trend and challenges of teaching and assessment to supports teachers ‘Professional growth.